PERANCANGAN MAJALAH FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI PADANG - PUTRI RAHMI, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The purpose of this scheme is to design the Faculty of Language and Art magazine Padang State  University as a media publication informative and communicative in order to fulfill all the information about all the activities that exist in the environment Faculty of Language and Art. Data analysis  method used is the analysis technique 5W + 1H, which is what, who, where, when, why, how. Data is collected using the method of observation interviews and documentation. Faculty of Language and  Arts Magazine Padang State University is designed to use the theory of Visual Communication  Design, media, magazines theory, layout, and color. In addition to the design of the Faculty of  Language and Art magazine Padang State University as the main media, this design is also supported by several media such as posters, x-banner, calendar, zipper pouch, tote bag, t-shirt, and a pen.Keywords: Design, Magazine, Faculty of Language and Art, University of Padang